Time series prediction : design, testing and optimisation using genetic search methods - Ng, Cheng Piaw. (2008)
The process of specifying a prediction model involves selecting the variables to be included, selecting the form of the equation of relationship, and estimating the values of the parameters in that equation. After the model has been specified, its performance characteristics should be further verified or validated by comparison of its prediction with historical data for the phenomenon it was designed to predict.